Eligibility to Use the Fund's Facilities for Concessinal Financing. (Policy Papers; Policy Paper, 2013)
During the 2012 Review of Poverty Reduction and Growth Trust (PRGT) Eligibility, Executive Directors expressed a number of concerns about the eligibility framework. The Board decided to bring forward the next review of eligibility by one year, to early 2013, in light of these concerns. In particular, Directors called for the review to assess: Possible shortcomings of the gross national income (GNI) per capita criterion in the case of small states, and whether additional or alternative variables should be used to better capture members' circumstances, particularly those of small states; as well as further options to enhance the flexibility of the PRGT-eligibility framework to cover small and very small countries; The application of the short-term vulnerabilities criterion for graduation, which can lead to repeated non-graduation of members that meet either the income or the market access criteria for graduation.